The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsomega.0c02330
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Amorphous Interphase in Poly(l-lactic acid): Estimation of the Tensile Elastic Modulus

Abstract: The mechanical properties of semicrystalline PLLA containing exclusively α′- or α-crystals have been investigated. The connection between experimental elastic moduli and phase composition has been analyzed as a function of the polymorphic crystalline form. For a complete interpretation of the mechanical properties, the contribution of the crystalline regions and the constrained amorphous interphase or rigid amorphous fraction (RAF) has been quantified by a three-phase mechanical model. The mathematical approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 75 publications
5
24
0
Order By: Relevance
“…From the plots of loss tangent (tan δ) ( Figure 4 ) as a function of temperature, it can be observed that the fibers addition slightly shifts the temperature position of the tan δ peak and also slightly lowers the magnitude of the peak that becomes broad. The variation of the tan δ peak is generally correlated to the interaction between the fillers and the matrix that reduces the polymer chains’ mobility [ 77 ]. With the tan δ variation not marked, also, the matrix–filler interaction is not intense, also confirming the results of the mechanical tests.…”
Section: Resultsmentioning
confidence: 99%
“…From the plots of loss tangent (tan δ) ( Figure 4 ) as a function of temperature, it can be observed that the fibers addition slightly shifts the temperature position of the tan δ peak and also slightly lowers the magnitude of the peak that becomes broad. The variation of the tan δ peak is generally correlated to the interaction between the fillers and the matrix that reduces the polymer chains’ mobility [ 77 ]. With the tan δ variation not marked, also, the matrix–filler interaction is not intense, also confirming the results of the mechanical tests.…”
Section: Resultsmentioning
confidence: 99%
“…This interphase is named the rigid amorphous fraction ( X RAF filler ) [ 35 ], in reference to the similar behavior commonly reported at the crystal/amorphous interface ( X RAF crystal ). It is known that X RAF crystal strongly affects the macroscopic properties, such as mechanical or barrier properties [ 36 , 37 ]. Klonos et al [ 38 ] showed that X RAF filler hinders thermal diffusivity, whereas X RAF crystal facilitates heat transport.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Recent studies have demonstrated that the rigid amorphous fraction inuences the performance of semi-crystalline polymers, because many physical properties of the RAF are different from those of the crystalline and the mobile amorphous fractions. [28][29][30][31][32][33][34][35] Experimental evidences and theoretical modelling have demonstrated that the elastic modulus of the RAF (E RA ) is between those of the crystalline (E C ) and mobile amorphous (E MA ) fractions, in the order E MA < E RA < E C . 29,31,32 On the other hand, the density of the RAF (r RA ) is lower than that of the MAF (r MA ), due to the higher RAF vitrication temperature, 32,33 so that the order of the densities turns out to be r RA <r MA <r C , where r C is the density of the crystalline phase.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35] Experimental evidences and theoretical modelling have demonstrated that the elastic modulus of the RAF (E RA ) is between those of the crystalline (E C ) and mobile amorphous (E MA ) fractions, in the order E MA < E RA < E C . 29,31,32 On the other hand, the density of the RAF (r RA ) is lower than that of the MAF (r MA ), due to the higher RAF vitrication temperature, 32,33 so that the order of the densities turns out to be r RA <r MA <r C , where r C is the density of the crystalline phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation